1998
DOI: 10.1177/002215549804601109
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Heat Shock Proteins in Mouse Skin During Wound Healing

Abstract: SUMMARYWound healing conditions generate a stressful environment for the cells involved in the regeneration process and are therefore postulated to influence the expression of heat shock proteins (Hsps). We have examined the expression of four Hsps (Hsp27, Hsp60, Hsp70 and Hsp90) and a keratin (keratin 6) by immunohistochemistry during cutaneous wound repair from Day 1 to Day 21 after wounding in the mouse. Hsps were constitutively expressed in normal mouse epidermis and their patterns of expression were modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
114
0
8

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(131 citation statements)
references
References 77 publications
(92 reference statements)
9
114
0
8
Order By: Relevance
“…During mouse embryonic development, Hsp27 is transiently expressed at the onset of myogenic differentiation in the cardiac primordium and in the myotomes (Gernold et al, 1993;Loones et al, 1997), as well as in certain neurons of the central nervous system (Gernold et al, 1993;Arrigo and Mehlen, 1994). Also, the expression of Hsp27 in some renewing cell populations of adult mice and rats, including chondrocytes of the growth plate (Tiffee et al, 2000), keratinocytes of the epidermis and other stratified squamous epithelia (Laplante et al, 1998;Wakayama and Iseki, 1998), and testicular germ cells (Wakayama and Iseki, 1999) is indicative of the involvement of Hsp27 in cell differentiation. In the present study, we have demonstrated a transient expression of Hsp27 in the differentiating acinar components of rat submandibular gland during postnatal development, providing further in vivo evidence for the role of Hsp27 in cellular transition from proliferation to differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…During mouse embryonic development, Hsp27 is transiently expressed at the onset of myogenic differentiation in the cardiac primordium and in the myotomes (Gernold et al, 1993;Loones et al, 1997), as well as in certain neurons of the central nervous system (Gernold et al, 1993;Arrigo and Mehlen, 1994). Also, the expression of Hsp27 in some renewing cell populations of adult mice and rats, including chondrocytes of the growth plate (Tiffee et al, 2000), keratinocytes of the epidermis and other stratified squamous epithelia (Laplante et al, 1998;Wakayama and Iseki, 1998), and testicular germ cells (Wakayama and Iseki, 1999) is indicative of the involvement of Hsp27 in cell differentiation. In the present study, we have demonstrated a transient expression of Hsp27 in the differentiating acinar components of rat submandibular gland during postnatal development, providing further in vivo evidence for the role of Hsp27 in cellular transition from proliferation to differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been reported that hsp70 and hsp90 are constitutively expressed in the epidermis. 104,105 These two heat-shock proteins are both able to inhibit the apoptosome formation, 106,107 and hsp70 can also antagonize the proapoptotic effects of apoptosis-inducing factor. 108 Overexpression of hsp70 can prevent UVB-induced apoptosis in an epidermal carcinoma line, 109 and hsp70-deficient mice are more susceptible to UVB-induced apoptosis.…”
Section: Mitochondrial Factors and Apoptosome Formationmentioning
confidence: 99%
“…Since TAMs show enhanced activity upon activation hsp70, as our observations confirm, this might be preactivated or raged macrophages, which could be of relevance in immunotherapeutic protocols against malignancies. Normally, most of the hsp70 that are constitutively synthesized and localized in the cytosol are expressed and induced in inflammatory conditions (28)(29)30) such as in malignancies and other diseases. Necrosis of these inflamed cells provides highly local concentration ofhsp70 in extra cellular microenvironment for stimulation of an immune response.…”
Section: Effect Ofh~p 70 On Inos Gene Expressionmentioning
confidence: 99%